2015
DOI: 10.1007/s00408-015-9700-3
|View full text |Cite
|
Sign up to set email alerts
|

Aging of the Lungs in Asymptomatic Lifelong Nonsmokers: Findings on HRCT

Abstract: Parenchymal bands, ground-glass opacities, septal lines, bronchiectasis, micronodules, reticular opacities, and lung cysts were more prevalent among the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 28 publications
2
30
1
3
Order By: Relevance
“…In the studies by Copley et al 3 and Winter et al 4 with relatively small numbers of subjects, only the elderly groups (older than 65 or 75 years) had pulmonary cysts. The present study of a large population-based cohort revealed that pulmonary cysts can be seen even in middle-aged participants as young as 40 years.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the studies by Copley et al 3 and Winter et al 4 with relatively small numbers of subjects, only the elderly groups (older than 65 or 75 years) had pulmonary cysts. The present study of a large population-based cohort revealed that pulmonary cysts can be seen even in middle-aged participants as young as 40 years.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, our study involved a direct comparison of the groups with emphysema and pulmonary cysts separately diagnosed on CT and revealed that these two entities occur independently. In the previous studies, it was not possible to discuss the association between age-related pulmonary cysts and emphysema because the presence of chronic lung diseases including emphysema was a part of exclusion criteria 3 4 6 17. Furthermore, some other findings also bolster the fact that pulmonary cysts are a distinct entity from emphysema: pulmonary cysts are not associated with smoking and tend to occur with the lower lobe predilection with no sex difference and no impairment of measures of spirometry, whereas emphysema predominantly occurs in the upper lobes, in male smokers 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological bronchiectasis may be a common finding in the asymptomatic elderly or may be an incidental finding in other respiratory disorders such as COPD [2426]. For the avoidance of doubt, patients with radiological bronchiectasis but without clinical symptoms and a physician diagnosis of clinically significant bronchiectasis will not be included in the study.…”
Section: Methods and Design Of The Embarc Registrymentioning
confidence: 99%
“…5). [37][38][39][40] The frequency and extent of air-trapping (an indirect CT feature of small airways disease) significantly increased with age in a prospective study by Lee et al, 40 but relatively few over 75 years olds were included. 34 Airways Multiple CT studies have described both large and small airway "abnormalities" in apparently healthy older individuals.…”
Section: Ct Parenchymal and Airway Features Described In Older Peoplementioning
confidence: 99%